2019
DOI: 10.1038/s41598-019-51907-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low doses of biocides on the antimicrobial resistance and the biofilms of Cronobacter sakazakii and Yersinia enterocolitica

Abstract: The susceptibility of Cronobacter sakazakii ATCC 29544 (CS) and Yersinia enterocolitica ATCC 9610 (YE) to sodium hypochlorite (10% of active chlorine; SHY), peracetic acid (39% solution of peracetic acid in acetic acid; PAA) and benzalkonium chloride (BZK) was tested. Minimum inhibitory concentration (MIC) values (planktonic cells; microdilution broth method) of 3,800 ppm (SHY), 1,200 ppm (PAA) and 15 ppm (BZK) for CS, and 2,500 ppm (SHY), 1,275 ppm (PAA) and 20 ppm (BZK) for YE, were found. In some instances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Data regarding the strains’ pathogenicity are of high interest if correlated to antimicrobial resistance or tolerance to biocides. In this respect, a recent study demonstrated the ability of Ye to acquire tolerance to biocides and to increase its antibiotic resistance after exposure to sub-MICs of such disinfectants [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the strains’ pathogenicity are of high interest if correlated to antimicrobial resistance or tolerance to biocides. In this respect, a recent study demonstrated the ability of Ye to acquire tolerance to biocides and to increase its antibiotic resistance after exposure to sub-MICs of such disinfectants [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to low concentrations of biocides remains a poorly understand risk factor for the development of decreased antibiotic and biocide susceptibility. Previous studies have shown that long-term exposure to biocides in drains resulted in little alteration in antimicrobial susceptibility (47)(48)(49), but other experiments have indicated that lowlevel biocide exposure leads to cross-tolerance to other disinfectants or antibiotics (20,40,50). Therefore, more studies are required to fully understand the role of environmental biocide exposure on bacterial adaptation and potential progression toward tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, improper use (spraying, fogging streets or marketplaces, sidewalks, tunnel, cabinet, chamber, and full-body spray) of biocides, like cationic agents and triclosan, has been reported [ 9 ]. Such disinfecting agents are known to select for antibiotic-resistant bacteria and can have a broad impact on the environment and human and animal health [ 13 , 14 ]. The ability of biocides, such as triclosan, to activate multidrug efflux pumps contributes to AMR by selecting bacteria that are resistant to a spectrum of antibiotics [ 10 , 17 , 46 ].…”
Section: The Broader Use Of Biocidal Agentsmentioning
confidence: 99%